IDENTIFY MENSTRUATION RELATED PROBLEMS AND SUICIDE - Alan, Sultan; Bakir, Emine; Surucu, Sule GOKYILDIZ; Yildirim, Emine (LIFE: International Journal of Health and Life-Sciences, 2018)
Research Motivation: The most common symptoms of premenstrual syndrome are uneasiness, stress, inability to control anger, fatigue, dizziness, increased appetite, anxiety, decrease in concentration, breast tenderness and swelling, muscle and joint painResearch Objectives: The study aims to identify menstruation related problems of women who are hospitalized due to a suicide attempt.Methodology: The study was conducted in Emergency Service of Balcali Hospital, Cukurova University. The population consisted of all women between the ages of 15-49 (n=70) who attempted to suicide and applied to the hospital. The data were collected via a questionnaire prepared by the researchers and Menstrual Distress Questionnaire developed by Rudolf H. Moos.Findings: 65.7% of the participants were between the ages of 15 and 25, and more than half had complaints regarding premenstrual distress for two cycles. It was noted that the highest rate of support came from parents and close relatives of the participants and the rate for professional support was rather low. The analysis of responses to menstrual distress questionnaire revealed that the last menstrual period had the highest average score of 33.57±32.95. The analysis of sub-dimensions indicated that pain sub-section had the highest average score while autonomic reaction sub-dimension had the lowest average score regarding menstrual distress.Research Outcomes and Future Scope: The study indicated that more than half of the women who were hospitalized following a suicidal attempt was young and more than half had complaints regarding premenstrual distress for two cycles. It can be recommended for health professionals to evaluate, educate and guide young people about menstruation, potential changes in the body and coping methods.